Cost optimization of electricity in energy storage system by dynamic programming - Mishra, Debani Prasad; Routray, Bhabesh; Pattanayak, Nitesh; Shekhar, Priyansu; Behera, Pratyus Ranjan; Salkuti, Surender Reddy (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper presents a dynamic programming solution for the cost optimization of an electric storage system. The objective is to minimize the total cost of meeting electricity demand over a specified time interval, considering energy constraints and costs. The proposed algorithm efficiently determines the optimal energy discharge and charge strategies for the storage system, resulting in reduced overall costs. The effectiveness and efficiency of the algorithm are demonstrated through various test cases, highlighting its potential for real-world applications in energy storage systems and electric grid management. It also provides an overview of different types of electrical storage systems, review recent research on optimization techniques for energy storage, and examines recent studies on the optimization of electrical storage systems for specific applications, such as peak load shaving and grid stability. Through this comprehensive analysis, we hope to shed light on the current state of the field and identify areas for further research and improvement.